THE EFFECTIVENESS OF THE USE OF QUIZIZZ-BASED GAMIFICATION ON STUDENTS’ LEARNING INTEREST IN 4TH GRADE MATHEMATICS - Elvira Maulidya; Kiki Aryaningrum; Ali Fakhrudin (JPSD (Jurnal Pendidikan Sekolah Dasar), 2022)
Abstract The learning interest of 4th grade students at SD Muhammadiyah 16 Palembang in mathematics is still low due to online learning media factors that are less attractive and conventional learning (questions and answers, and assignments). This research aims to determine students’ learning interest before and after using Quizizz-based gamification and to determine the effectiveness of using Quizizz-based gamification on students’ interest in 4th-grade mathematics learning. This research uses experimental quantitative methods. The population in this research was all 4th grade students as the experimental and the control class. The results of the research using the t-test and the N-Gain test showed that ttable 2,000 and tcount 6.104 from the results of the independent sample t-test on students’ interest in learning is tcount > ttable. So Ha is accepted and Ho is rejected. While the N-Gain test in the experimental class is 0.77 and the control class is 0.50. It can be concluded that the use of Quizizz-based gamification is effective on students’ interest in mathematics learning in the 4th grade of SD Muhammadiyah 16 Palembang. Keywords: Quizizz Gamification; Learning Interest